Perfil sociodemográfico, nutricional e psicossocial dos usuários dos restaurantes e refeitório populares de Belo Horizonte-MG: fundamento para a elaboração de uma intervenção educativa alimentar e nutricional - Isabel Cristina Bento (2012)
Introduction: Low Cost Restaurant Program recommends that these establishments function as spaces for the dissemination and implementation of food and nutrition education, to encourage the practice of healthy eating habits and contribute to disease prevention and healthpromotion. The practices of food and nutrition education today are driven in the transmission of information, and do not favor the creation of new meanings for the act of eating and the redefinition of practices that lead to the autonomous development of strategies for the acquisition of a healthy diet. It is observed that is necessary, beyond the quest for knowledgeconstruction, consider the subjective dimension of eating behavior and the social-cognitive theories, and socio-demographic factors and nutritional. Objective: To determine the demographic, nutritional and psychosocial profile of users of the low cost restaurants andcanteen of Belo Horizonte-MG, and develop a food and nutrition education intervention based on this profiles and the processes of the transtheoretical model. Method: This is a cross sectional study of quantitative and qualitative approach with 1656 users of four low costrestaurants and one canteen in Belo Horizonte-MG.The sample was calculated after measuring the flow of users in each establishment according to gender, age and type of meals (breakfast, lunch and dinner). Data were collected by quotas according to gender, age and meals made by establishment. It was determined the sociodemographic and nutrition profiles and the stages and phases of change in the behavior of users, through a structured questionnaire. It was used a semi-structured questionnaire to identify the social representations. Data analysis wasperformed with the use of descriptive statistics, using the SPSS version 19.0. There was also the use of discourse analysis of the collective subject. With these data identified, it was conducted an educational intervention. Results: The users who frequent the low costrestaurants and canteen are predominantly male, workers, mean age 42.34 ± 16.69 years, low socioeconomic class, no marital status, and no partner level educational medium. A considerable portion of users have proper weight and regular eating habits. The study highlightsthe high prevalence of overweight and regular eating habits. The most prevalent stage of change are maintenance and precontemplation, respectively. Users share the social representations that to have a healthy diet, they should regularize the timing of meals, theyshould eat more often during the day, and they should chew their food thoroughly. Still, they should cut and reduce foods high in carbohydrates and fats. Regarding the difficulties to obtain such behavior, they pointed out lack of financial resources, and lack of time to prepare and buyhealthy foods. The educational intervention had a healthy diet as a general theme, with emphasis on consumption of fruits and vegetables. It was employed as a method of teaching the theory of John Dewey's educational experience and the soap operas strategy. Conclusion:It is possible to develop an educational approach that is in line with the ideal of behavior change considering the social representations and socio-cognitive-behavioral target and take into account the intellectual and emotional dimension of learning.